Prevalence and Identification of Coccidian Parasite (Eimeria Spp) in Layer Chicken of Ratnanagar Municipality, Chitwan District, Nepal - Adhikari, Arjun; Gupta, Ranjana; Pant, Ganesh Raj (Journal of Natural History Museum, 2009)
Five different species of Eimeria viz. E. acervulina, E. maxima, E. necatrix, E. tenella and E. brunetti were identified. The highest percentage (50%) was found with mixed infection. Specieswise infection with E. tenella was recorded in the present study. Monthwise highest prevalence rate (50%) was observed in March and the lowest (10%) in the months of April and September. Seasonwise prevalence showed the highest prevalence rate (33%) in the summer and spring, and the least (14%) in the autumn. The agewise prevalence was the highest (48%) in the 31-45 days age group and the least (6%) in 0-15 days age group of layers. The coccidiosis was found highly prevalence in mud/mud+brick type floor than in concrete type floor farms. Key words: Coccidiosis; Eimeria; infection; layers; percentage; summer; spring Journal of Natural History Museum Vol. 23, 2008 Page 45-50